A lateralized sensory signaling pathway mediates context-dependent olfactory plasticity in Caenorhabditis elegans - Anjali Pandey; Maya Katz; Stephen Nurrish; Alison Philbrook; Piali Sengupta (Proceedings of the National Academy of Sciences, 2026)
Lateralization of neuronal functions plays a critical role in regulating behavioral flexibility, but the underlying molecular mechanisms are challenging to establish at a single-neuron level. We previously showed that attraction of Caenorhabditis elegans to a medium-chain alcohol switches to avoidance in a uniform background of a second attractive odorant. This context-dependent behavioral plasticity is mediated by symmetric inversion of the odor-evoked response sign in the bilateral AWC olfactory neurons. Here, we show that this symmetric response plasticity is driven by asymmetric molecular mechanisms in the AWC neuron pair. Mutations in the gcy-12 receptor guanylyl cyclase abolish odor response plasticity only in AWC OFF ; the opposite odor-evoked response signs in AWC OFF and AWC ON in gcy-12 mutants result in these animals being behaviorally indifferent to this chemical. We find that gcy-12 is expressed, and required, in both AWC neurons to regulate odor response plasticity only in AWC OFF . We further show that disruption of AWC fate lateralization results in loss of asymmetry in the response plasticity in gcy-12 mutants. Our results indicate that symmetric neuronal response plasticity can arise from asymmetric underlying molecular mechanisms and suggest that lateralization of signaling pathways in defined conditions may enhance neuronal and behavioral flexibility.